Heterogenous preferences for agricultural landscape improvements in Southern Finland - Grammatikopoulou, Ioanna; Pouta, Eija; Salmiovirta, Maija; Soini, Katriina (it, 2011)
In planning landscape-related policy, such as agri-environmental measures, the European Landscape Convention emphasizes taking into account the population value and the place of various stakeholder groups in landscape benefits. In this study, a choice experiment was employed to evaluate a programme that provides certain landscape attributes in a typical agricultural area. The data from a municipality-level case study from southern Finland revealed that the most valued attributes were the renovation of production buildings and the presence of grazing animals. A latent class model with covariates indicated the existence of heterogeneous preferences regarding the utility received from landscape programmes, although the proportion of loosers did not exceed a fifth of the respondents.
Keywords: MA; maisemasuunnittelu; agricultural landscape; landscape design; choice experiment; latent class; heterogeneity